Vasco de Mello: análise de projetos não construídos - Macedo, Athur Justiniano de (2018)
The dissertation aims to analyze and discourse on eight unconstructed projects of the architect Vasco de Mello, and seek the influences of these projects in concrete works of previous or later date. This research was structured in four parts. The first chapter begins by presenting the previous researches on the architect Vasco de Mello, later it is exhibited a panorama of his career, showing the importance of his works in the architecture. Finally, it shows the concept used in the present study on the study of non-built projects, and the importance of this type of analysis when performing an examination of an architect's project landscape. In the second chapter the process and the pretext of choosing the works selected for the analysis is demonstrated, the methodology used in the research is also presented and the stages of redesign of the projects are explained, the analysis criteria are demonstrated In the third chapter, the eight projects selected for the research are exhibited, the iconographic material cataloged and the history of each work are exposed and an individual analysis of each project is performed. The fourth and final chapter is divided into comparative analyzes of case studies and analogies with constructed and non-constructed projects. The study is developed from the collection of the architect that was cataloged, systematized and digitized for the dissertation named "Vasco de Mello: percussion, panorama and analysis of his work" (2017) by Sandra Maalouli Hajli. Vasco de Mello has 459 works in his curriculum, and despite his extensive architectural production, there are no previous studies that contemplate the analysis and importance of his unbuilt projects.